Balloon madness : flights of imagination in Britain, 1783-1786 - Brant, Clare, 1960- (Boydell Press, 2017)
"'All the world is mad about balloons' observers recorded during the craze in Britain that lasted from 1783 to 1786. Excitement about the new invention spread rapidly, inspiring hopes, visions, fashions, celebrations, satires, imaginary heroics and real adventures. In this sparkling account, Brant uses the brief moment of balloon madness as a way into a wide-ranging exploration of Enlightenment sensibility in Britain. She follows the craze as it travelled around the country, spread through crowds and shaped the daily lives and dreams of individuals. From the levity of fashion, political satire and light verse inspired by balloons, she shows how wonders of air and speed also connected with the deeper preoccupations and anxieties of eighteenth-century Britain. An aerial 'view from above' provided new moral perspectives on the place of humans in the universe and the nature of their aspirations; while the success of the French, leaders in aeronautics, unsettled national identity with visions of a new world order. The practical limitations of balloons soon put an end to one set of possibilities, but their effect on popular culture was more enduring, with meaning even today. With a cast including kings, politicians, charlatans, pickpockets, the beau monde, duellists and animals, Balloon Madness celebrates the excitement and fun of this brief but world-changing episode of history and its long afterlife in our imagination."--Amazon